The Mekong : - Hori, Hiroshi (United Nations, 2000)
This informative and critical account of the experience in planning for development of the water resources of the Mekong basin is unique in at least two respects: it describes the Mekong experience; it also provides a concrete demonstration of how international thinking and action on water management evolved over the years following 1958. The Mekong describes what was done, and why, while encouraging thoughtful evaluation of possible lessons for use elsewhere. This book provides a comprehensive description of the basin and of unfolding policies for its development.